Ancient Manuscripts in Digital Culture Visualisation, Data Mining, Communication - Hamidović, David; Clivaz, Claire; Bowen Savant, Sarah (Digital Biblical Studies, 2019)
Ancient Manuscripts in Digital Culture presents an overview of the digital turn in Ancient Jewish and Christian manuscripts visualisation, data mining and communication, edited by David Hamidović, Claire Clivaz and Sarah Bowen Savant. Readership: Scholars and PhD and master students in Biblical studies, Early Jewish and Christian studies.